Economic strategies for a thriving Danube Region - Zuzana Zavarská (The Vienna Institute for International Economic Studies (wiiw), 2024)
This policy note explores key issues in the Danube Region, focusing on labour market dynamics, including the development of digital skills, foreign direct investment (FDI) with a particular emphasis on FDI in the IT sector, and the robotisation and automation of the region's industries. Covering 14 countries-Austria, Bosnia and Herzegovina, Bulgaria, Croatia, Czechia, Germany, Hungary, Moldova, Montenegro, Romania, Serbia, Slovakia, Slovenia, and Ukraine-it outlines policy recommendations aimed at enhancing workforce readiness, attracting high-tech foreign investments, and ensuring the region's competitiveness in an increasingly digitalised and automated global economy.
Keywords: O52; R58; F21; J24; O33; 330; Danube Region; Austria; Bosnia and Herzegovina; Bulgaria; Croatia; Czechia; Germany; Hungary; Moldova; Montenegro; Romania; Serbia; Slovakia; Slovenia; Ukraine; Economic Policy; FDI; Digitalisation; Automation; Labour Market Dynamics; Regional Development